Emotion : A Very Short Introduction - Evans, Dylan 1966- (Karachi Oxford University Press, 2003)
"Was love invented by European poets in the Middle Ages or is it part of human nature? Will winning the lottery really make you happy? Is it possible to build robots that have feelings? These are just some of the intriguing questions explored in this guide to the latest thinking about the emotions. Drawing on a wide range of scientific research, from anthropology and psychology to neuroscience and artificial intelligence, this Very Short Introduction takes the reader on a fascinating journey into the human heart."--Jacket.
Include Pictures and Index
Keywords: Emotions -- Emotions (Philosophy)